A Critical View on the Processes of Robotization in Companies (Journal of Universal Excellence, 2026)
Research Question (RQ): Robotization has many effects on our society, which, on the one hand, are expressed in potential benefits, on the other hand they represent a risk to society. Therefore, important question occurs: ""What are the effects of robotization on the need for human labour and hence to unemployment?"Purpose: The purpose of the article is to give a critical view of the research question raised. In a critical discussion, I will begin by focusing on the explanation of the word robot, robotization, and consequently on positive as well as negative aspects of robotization. Some authors argue that robotization is not very different from other technologies that support automation and higher productivity. Others feel that robots can replace people at work. Explanations and insights by various authors on the course of robot development and robotization are clearly summarized. At the conclusion of the discussion, I gave a critical look at the introduction of robotics and robots into the working environment.Method: The article uses the critical discourse method. The findings are based on meta-analysis. Content review of the articles was used to summarize and compare qualitative data.Results: The advantage of robotization is primarily in the replacement of employees at workplaces that endanger the health of workers and where dangerous working conditions prevail. On the negative side, it represents a job placement, which can be performed by a empoyee without major problems. The robot then puts the worker in an unequal position, as the robot lowers the value of work, it is almost infallible and has no problems with absenteeism, poor interpersonal relationships, family, and so on.Organization: Management must be aware of the changes brought about by the robotization process.Society: The process of robotization can affect the occurrence of negative consequences for employment. The article highlights areas in which we need to be careful when introducing robotization.Originality: The originality is in the presentation of a critical view of the process of robotization in Slovenia.Limitations / further research: The article represents a critical view of the robotization process, the research was not done.
Keywords: robot; robotization; Industry 4.0; human labour